2001
DOI: 10.1089/08977150152693755
|View full text |Cite
|
Sign up to set email alerts
|

Acidosis Promotes the Permeability Transition in Energized Mitochondria: Implications for Reperfusion Injury

Abstract: We have studied the influence of pH on opening of the mitochondrial permeability transition pore (PTP) in both deenergized and energized mitochondria in the presence of Pi. In deenergized mitochondria from rat brain and heart, we observed the expected inhibition of Ca2+-induced PTP opening at increasingly acidic pH values. Unexpectedly, mitochondria energized with either electron transport complex I or complex II substrates displayed the opposite behavior, acidic pH promoting rather than inhibiting PTP opening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
53
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 57 publications
2
53
0
Order By: Relevance
“…The reason(s) for extreme variability of mitochondrial Ca 2ϩ uptake is unknown but may reflect mitochondrial location or local [Ca 2ϩ ] i fluctuations (Rizzuto et al, 2000). Alternatively, [Ca] mito heterogeneity between individual mitochondria could plausibly reflect fluctuations in ⌬⌿ m (Buckman and Reynolds, 2001;Collins et al, 2002) or the availability of inorganic phosphate (Kristian et al, 2001;Chalmers and Nicholls, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The reason(s) for extreme variability of mitochondrial Ca 2ϩ uptake is unknown but may reflect mitochondrial location or local [Ca 2ϩ ] i fluctuations (Rizzuto et al, 2000). Alternatively, [Ca] mito heterogeneity between individual mitochondria could plausibly reflect fluctuations in ⌬⌿ m (Buckman and Reynolds, 2001;Collins et al, 2002) or the availability of inorganic phosphate (Kristian et al, 2001;Chalmers and Nicholls, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study shed light on this issue. Using energized mitochondria preparation from both brain and heart, Kristiá n et al (35) demonstrated that acidosis promotes, rather than prevents, the formation of the MPT under conditions mimicking those occurring in vivo in terms of mitochondrial calcium content, P i concentration, and pH value. We have also previously observed that hyperglycemia causes mitochondrial swelling at early reperfusion phase as detected by electron microscopy (16).…”
Section: Discussionmentioning
confidence: 99%
“…This is based on the increased uptake of inorganic phosphate (HPO 4 2− ) driven by the proton motive force across the inner mitochondrial membrane (Kristian et al, 2001). It is via this larger mitochondrial Ca 2+ load that acidosis favors the opening of the mPTP (Kristian et al, 2001) and thus paves the way for irreversible cell damage and cell loss.…”
Section: Ph Effectsmentioning
confidence: 99%
“…This is based on the increased uptake of inorganic phosphate (HPO 4 2− ) driven by the proton motive force across the inner mitochondrial membrane (Kristian et al, 2001). It is via this larger mitochondrial Ca 2+ load that acidosis favors the opening of the mPTP (Kristian et al, 2001) and thus paves the way for irreversible cell damage and cell loss. Such pH-mediated distortion of mitochondrial function could contribute to the glucose paradox of cerebral ischemia, i.e., the fact that the outcome of cerebral stroke is worse for patients suffering from diabetes mellitus and hyperglycemia, in spite of the apparent benefit which hyperglycemia should provide in anoxic conditions (Schurr et al, 2001).…”
Section: Ph Effectsmentioning
confidence: 99%